Contribution of Lean Manufacturing on environmental performance in Moroccan Industry - Yassine Bouazza; Azza Lajjam (Logistic and Operation Management Research (LOMR), 2023)
In the context of globalized competition, sustainable development has become a crucial goal for manufacturers, necessitating a balance between economic, environmental, and social factors. The evolution of production system efficiencies and government policies has been pivotal in mitigating the environmental impact of manufacturing activities. This paper explores the role of Lean Manufacturing in enhancing environmental performance within organizations. It presents the concept, tools, and models of Lean Manufacturing, discussing its contribution to environmental sustainability. The paper bases its findings on a literature review and validates them through two case studies in Morocco. The first case study examines the implementation of Lean tools in a Tangier-based company, highlighting significant reductions in waste and energy consumption. The second involves interviews with managers from Moroccan automotive industries, revealing a positive correlation between Lean practices and environmental performance. The conclusion drawn is that Lean Manufacturing not only reduces pollution and energy consumption but also boosts productivity, thus aiding companies in becoming more profitable and environmentally responsible.